Dispersion, solvent and metal effects in the binding of gold cations to alkynyl ligands: implications for Au(i) catalysis1. Issue 47 (14th June 2015) - Ciano, Luisa; Fey, Natalie; Halliday, Connor J. V.; Lynam, Jason M.; Milner, Lucy M.; Mistry, Nimesh; Pridmore, Natalie E.; Townsend, Nell S.; Whitwood, Adrian C.
<x xml:space="preserve">Abstract</x> The ability of gold(i) cations to coordinate to alkynyl ligands allows for the formation of di- and trinuclear scaffolds. This reinforces the notion that multiple gold coordination may play a key role in catalysis.